Boosting optical performance of polymer embedded phosphors using iodine-free and iodine-decorated sol-gel synthesized alpha-Fe2O3 - (:unkn) unknown (ELSEVIER, 2019)
In this work spectral properties of the commercially available green, yellow and red phosphors; Lu3Al5O12: Ce3+(LuAG); (Y,Gd)(3)Al5O12: Ce3+ (YAG) and CaAISiN(3): Eu2+ (CASN); have been have been improved utilizing cost-effective hematite particles. Excitation and emission spectra of the hematite (HEM) and iodine decorated hematite (I-HEM) incorporated phosphors were recorded in poly methyl methacrylate matrix in form of thin films. When tested along with the nano-scale HEM particles, the LuAG exhibited 16 nm of red shift and 53-fold enhancement in the signal intensity. Incorporation of the HEM and I-HEM with the YAG resulted in two and 200-fold enhancement in the emission intensity of the phosphor, respectively. The CASN exhibited 24 and 27-fold enhancement in the luminescence intensity when embedded along with the HEM and I-HEM. Presence of the related particles in close proximity with the CASN increased the emission intensity of the phosphor 24 and 27-fold, respectively. The HEM significantly enhanced efficiency of the F-2(5/2) -> 5 d(2) and F-2(7/2) -> 5 d(1) transitions of the Ce (3+) in the cerium activated phosphors. All of the phosphors exhibited three exponential and longer decay times when incorporated with the HEM or I-HEM with respect to their individual states.
Keywords: Green; Yellow; Red phosphor; LuAG; YAG; CASN; Hematite; Iodine; LIGHT; PHOTOLUMINESCENCE